What Do Consumers Think About Your Brand? Just Ask! - Lucas Nann; David Finken; Adnan Zogaj; Stefan Reiser; Reto Hofstetter (Marketing Review St.Gallen, 2023)
Tracking consumer perceptions over time is a crucial component of brand success. Yet, many companies struggle to do so because continuous consumer surveying is costly and challenging. Building on established research about consumer-based brand equity, this article presents a practical approach to monitoring consumer perceptions continuously.
Keywords: 650